Enhancing Outdoor Equipment Marketing through Augmented Reality: A Case Study of Sekaben Camp - Sugihartono, Tri; Putra, Rendy Rian Chrisna; Dwi Sandro, Irsad (ISB Atma Luhur, 2024)
Augmented Reality (AR) has the potential to transform product marketing by creating immersive and interactive experiences. This study presents the development of an AR-based application to enhance the marketing of outdoor equipment at Sekaben Camp, a camper rental company in Pangkalpinang, Bangka Belitung. The application allows users to visualize and interact with three-dimensional (3D) models of rental gear on their Android smartphones, making the selection process more engaging and informative. Using a prototyping approach—an iterative process of building and refining a preliminary model—the research includes gathering requirements, developing a prototype, coding the system, testing, and final deployment. Key features such as AR scanning, equipment ordering, and a price listing interface were designed to enhance product visualization and user engagement. User testing revealed that 85% of participants found the application intuitive and reported a more realistic understanding of the gear's size and functionality, resulting in a 30% increase in customer satisfaction during the rental process.